Динамический анализ торцевых уплотнений ротора лабиринтно-винтового насоса - Андренко, Павел Николаевич; Лебедев, Антон Юрьевич; Григорьев, Александр Львович (НТУ "ХПИ", 2017)
Составлена математическая модель работы торцевого уплотнения с гладкими кольцами из релита в условиях жидкостного трения. Особенностью модели является учет теплового расширения жидкости в зазоре между кольцами; этот эффект, действующий совместно с силами трения, создает дополнительное давление и подъемную силу, зависящую от ширины зазора и скорости скольжения. В разработанной модели отображаются процессы выделения, переноса и отвода тепла в элементах уплотнения, а также используется сила сопротивления осевому перемещению кольца, возникающая в зазоре под действием насосного эффекта и трения в перетекающей жидкости; инерционность этой жидкости учитывается методом приведения масс. Выполнена линеаризация модели и получены динамические характеристики переходных процессов и вынужденных колебаний устройства. Сформулированы условия, накладываемые на параметры торцевого уплотнения для обеспечения режима жидкостного трения, что минимизирует износ.

A mathematical model of the work of the mechanical seal with smooth rings made from cast tungsten carbide in the condition of liquid friction is drawn up. A special feature of this model is the allowance for the thermal expansion of a liquid in the gap between the rings; this effect acting in the conjunction with the frictional forces creates additional pressure and lift which in its turn depends on the width of the gap and the speed of sliding. The developed model displays the processes of separation, transportation and heat removal in the compaction elements and also the resistance to axial movement of the ring arising in the gap caused by the pumping effect and the friction in the flowing liquid; the inertia of this fluid is taken into account by the mass reduction method. The linearization of the model is performed and the dynamic characteristics of the transient processes and the forced oscillations of the device are obtained. The conditions imposed on the parameters of the mechanical seal are formulated to provide a regime of the liquid friction, which minimizes the wear.
Dynamic analysis of the mechanical seals of the rotor of the labyrinth screw pump
Keywords: кольца из релита; жидкостное трение; насосный эффект; приведение масс; labyrinth screw pump; rotor mechanical seal; rings made from cast tungsten carbide; liquid friction; pumping effect; mass reduction method